Development of Pancasila Values-Based E-LKPD for Fifth Grade Elementary Students - Didik Wahyu Triono; Muhammad Nukman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study was conducted in response to the limited use of interactive digital learning media in Civic Education, particularly electronic student worksheets (e-LKPD) designed to foster Pancasila values among elementary school students. Previous studies have primarily focused on cognitive learning outcomes and have not specifically integrated contextual character education through interactive digital worksheets. Therefore, this study aimed to develop a Pancasila values-based e-LKPD for fifth-grade elementary students and determine its validity and practicality. This research employed a Research and Development (R&D) approach using the Four-D (4D) model, limited to the define, design, and develop stages. The study involved three expert validators consisting of a material expert, a language expert, and a design expert, as well as one fifth-grade teacher for the practicality test. Data were collected using validation sheets and teacher response questionnaires. The obtained data were analyzed using descriptive statistics based on percentages. The results showed that the developed e-LKPD achieved a very high level of validity, with scores of 92% from the material expert, 94% from the design expert, and 92% from the language expert. In addition, the teacher's practicality test scored 91%, indicating it was very practical. The developed e-LKPD integrates interactive activities, contextual learning tasks, reflective exercises, and multimedia features to support students' understanding and internalization of Pancasila values. The novelty of this study lies in integrating contextual character education and interactive multimedia elements into an e-LKPD specifically designed for elementary Civic Education learning. This study implies that digital-based learning media can support more meaningful, interactive, and character-oriented learning in elementary schools.